If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 4) + 5 = 0 Reorder the terms: -2(4 + x) + 5 = 0 (4 * -2 + x * -2) + 5 = 0 (-8 + -2x) + 5 = 0 Reorder the terms: -8 + 5 + -2x = 0 Combine like terms: -8 + 5 = -3 -3 + -2x = 0 Solving -3 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| x+2=7y | | 3x^2-12=0 | | 96=94p | | x-5/3=6 | | 50.50+18n= | | 2c+8=81 | | [2x+9]-10=5 | | -12-(x-3)=4x+5 | | 12+(3-2x)=-x | | X=(3)2 | | x^2+x+2=0 | | 12+(2x-3)=-x | | 3x^2-6y-39=0 | | 2x^2-2x-24=0 | | 3x^2-18x-39=0 | | 3x^2-18x+-9=0 | | (1/2x^5)6 | | 10y=-8x+5 | | -25=9+7(c-5) | | -2.30-0.60y=1.4 | | 2/9-8n^2 | | cos(2x)-3cos(x)+4=0 | | 20x-12y=28 | | 6s*39=141 | | 5x+13=6x | | 6s+39=141 | | 3(x+5)+2(x-3)=0 | | 2(1-4x)=-2(x+3)-4 | | 2-8x=-2x-6-4 | | -2.3+x=5.9 | | 2x+19=90 | | 1/2(16-x)=-12(x*7) |